How Indonesian Newspapers Covering Political Parties - Ibnu Hamad (Department of Communication Studies, Faculty of Social and Political Sciences Universitas, 2009)
Using a critical discourse analysis method, this research aims to find out pattern and background of 10 newspaper national wide covering 9 political parties in 1999 General Election Campaign. There is a similar way to construct the parties as a music group rather than a broker of the clearinghouse of ideas. They represent the political actors as famous celebrities. For the media, they have different interests with one another in the news making for each political parties, such as ideological, idealism, political, and economic or market factors.